There's an opossum in my backyard - Bogue, Gary (Heyday Books, 2007)
A baby opossum falls off its mother's back while traveling through the Green family's backyard and it spends the year there, learning about Rocky the dog, the cat next door, and the other wildlife in the yard. Includes facts about opossums, and related websites and books.